Estudo de variações bioquímicas e genotoxicidade induzidas por mistura de contaminantes em tilápia (Oreochromis niloticus), como biomarcadores de contaminação ambiental - Rodrigues, Aline Cristina Ferreira [UNESP] (2014)
Water quality is of fundamental importance in ecotoxicological context because the aquatic environments are the main destinations of thousands of chemicals for daily use that can act as potential distorters of these ecosystems. In this context we highlight the pesticides such as organophosphates (OP) and pyrethroid (PI), endocrine disrupters such as 17β-estradiol (E2) and polycyclic aromatic hydrocarbons (PAHs) such as benzo(a)pyrene (BaP). Studies on metabolic responses in organisms subjected to different classes of contaminants are extremely valuable to elucidate the effects of the toxicity of mixtures, known as cocktail effect. The main objective of this study was to evaluate in tilapia (Oreochromis niloticus) the effects of mixtures of BaP, E2, and pesticides diazinon (OP) and cypermethrin (PI) in biomarkers of detoxication, oxidative stress, esterase activity and genotoxic potential. Another objective was to monitor the water quality of the Tietê River that runs through the Araçatuba – SP, sugarcane area of intense activity and nautical condominiums through the same biomarkers, field to apply the methodology used in the laboratory for environmental diagnosis. The concentrations used were 10 μg.L-1 of BaP; 220 μg.L-1 of OP; 0.5 μg.L-1 de PI; 0.5 μg.L-1 of E2 (mixture at low concentration); 100 μg.L-1 BaP, 500 mg.L-1 of OP; 1.5 μg.L-1 of PI; 2.5 μg.L-1 of E2 (mixture at high concentration); 100 μg.L-1 of BaP; 500 μg.L-1 of OP; 1.5 μg.L-1 of PI; 2.5 μg.L-1 of 17 E2. Exposures to the four contaminants mixed for 5 days were preceded, pre-exposure to BaP for 3 days followed by exposure to E2 for 5 days; pre-exposure to E2 for 3 days followed by exposure to BaP for 5 days, and pre-exposure to BaP and E2 individually for 3 days followed by exposure to the pesticide individually and mixed for 5 more days. The activities of glutathione S-transferase and carboxylesterase, and malondialdehyde and reduced glutathione ...